Intrapartum Ultrasound in Maternal Lateral Position. A Prospective Observational Study - Marcos Javier Cuerva; Elena Rodriguez; Francisco Lopez; José Luis Bartha (IMR Press, 2022)
Background: Intrapartum ultrasound (ITU) techniques have been described only in maternal semi-recumbent position. However, other birthing positions, such as side-lying, are more comfortable for many mothers. The present study aimed to test the hypothesis that ITU measurements can be obtained in maternal lateral positions during the second stage of labor. Methods: A single-center, prospective observational study was conducted. Women who preferred a side-lying position during the second stage of labor participated in the study. The women were asked to grasp their upper knee and flex it to perform the ultrasound scan. The transducer was first placed in the frontal plane and then rotated to the midsagittal plane (the probe was placed at the level of the fourchette). Results: 34 women participated in the study. Position of the fetal head, angle of progression, and head-perineum distance with and without contraction were obtained in all women. There was a moderate correlation between the head-perineum distance with contraction and the ITU to birth time (r = 0.466; p = 0.009). Conclusions: ITU in maternal lateral position (side-lying) is a simple technique that avoids unnecessary changing of position during the second stage of labor.